Carver, Cavell, and the Uncanniness of the Ordinary - Forsberg, Anders Niklas (Johns Hopkins University, 2018)
A predominant misunderstanding of the philosophical importance of paying attention to our ordinary language is that it supplies us with a standard of correctness. In contrast to this view, it is arguedhere that everyday and ordinary language are so difficult to bring into view and that this is something both J. L. Austin and Ludwig Wittgenstein maintained as well. It is precisely the failure to notice these kinds of difficulties that often leads philosophers into philosophical problems and metaphysical speculation. The philosopher who most clearly has stressed that "the everyday" is something difficult to get into view is Stanley Cavell, and he has also linked the concept of the ordinary to the Freudian concept of the uncanny. The idea of the "Unheimlich" contains the suggestion that there is something uncanny about that which is open to view because it is open to view. Thus, if the real problem with "ordinary language" is that we philosophers take ourselves to be in full command of our everyday language already and need not think more about it, then a presentation of our own familiar language that presents the familiar as something unfamiliar, the homely as strange, might be exactly what philosophy needs. This is one thing Raymond Carver's short stories achieve. The instability and flexibility here discerned does not warrant philosophico-theoretical "correction," but is rather a place where the complex, nuanced, and morally charged nature of our ordinary language comes into view. We are vulnerable to each other's wordings, but that vulnerability may itself be the very bond that holds us together.
Carver, Cavell, and the Uncanniness of the Ordinary
Keywords: Raymond Carver; Stanley Cavell; Ordinary Language Philosophy; Moral clarity; Moral language; vunerability